Evidence-based recommendations for the diagnosis and management of rheumatoid arthritis for non-rheumatologists: Integrating systematic literature research and expert opinion of the Thai Rheumatism Association - Wanruchada Katchamart (2018)
© 2016 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Aim: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease leading to joint damage, functional disability, poor quality of life and shortened life expectancy. Early diagnosis and aggressive treatment are a principal strategy to improve outcomes. To provide best practices in the diagnosis and management of patients with RA, the Thai Rheumatism Association (TRA) developed scientifically sound and clinically relevant evidence-based recommendations for general practitioners, internists, orthopedists, and physiatrists. Methods: Thirty-seven rheumatologists from across Thailand formulated 18 clinically relevant questions: three for diagnosis, 10 for treatments, four for monitoring, and one for referral. A bibliographic team systematically reviewed the relevant literature on these topics up to December 2013. A set of recommendations was proposed based on the results of systematic reviews combined with expert opinions. Group consensus was achieved for all statements and recommendations using the nominal group technique. Results: A set of recommendations was proposed. For diagnosis, either American College of Rheumatology (ACR) 1987 or ACR/European League Against Rheumatism 2010 classification criteria can be applied. For treatment, nonsteroidal anti-inflammatory drugs, glucocorticoid, and disease-modifying antirheumatic drugs, including antimalarials, methotrexate and sulfasalazine are recommended. Physiotherapy should be suggested to all patients. Tight control strategy and monitoring for efficacy and side effects of treatments, as well as indications for referral to a rheumatologist are provided. Conclusions: These evidence-based recommendations provide practical guidance for diagnosis, fundamental management and referral of patients with RA for non-rheumatologists. However, it should be incorporated with clinical judgments and decisions about care for each individual patient.